ANALISIS DAN RANCANG BANGUN APLIKASI ALAT BANTU MENGAJAR UNTUK GURU BERBASIS MULTIMEDIA DENGAN MENGGUNAKAN SOFTWARE ADOBE FLASH CS3 - Marhayu Marhayu (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
Applications of mathematics teaching aids at the pre - childhood is a multimedia -based applicationsthat can assist in the development process of learning . Semakain major technological developments sothat the need for recognition and knowledge of technology and it starts at an early age , especiallybeginning in Kindergarten - childhood .Applications of mathematics teaching aids on the level of kindergarten is an interactive multimedia -based learning model presentation using a methodology developed by Lutter as a method of developmentof multimedia applications , thematic method as a method of learning, learning plans that can supportmultiple intelligences of children and making use software of Adobe flash CS3 .Applications of mathematics teaching aids is an application that can assist teachers in the deliveryof materials on teaching and learning mathematics . The results of this application has some learningbasic menu is divided into 4 ( four) that the material recognition of numbers, geometry recognition ,addition, subtraction and accompanied with sample menus and tasks .